Kemungkinan Pemanfaatan Beberapa Jenis Rotan Non Komersial Ditinjau Dari Sifat-Sifat Fisik Mekanik - Heriad Daud S alusu; Eva Nurmarini; Ita Merni Patulak (Poltanesa, 2020)
This research was conducted to determine the basic properties of rattan which are related to the possibility of its use, which are physical-mechanical properties consisting of moisture content, density, parallel tensile strength and modulus of elasticity. There were 12 species of non-commercial rattan studied, 11 species included in the small diameter rattan category (<18 mm diameter) and 1 species belonging to the large diameter rattan category (> 18 mm diameter), namely Daemonorops korthlasii Blume. Based on the results of the tests carried out, there are three species of non-commercial rattan that have similar or similar basic properties to commercial rattan, namely Calamus conirostris Becc., Korthalsia ferox Becc., and Calamus muricatus Becc.